Komposisi Dan Struktur Vegetasi Riparian Di Kawasan Taman Wisata Gunung Poteng Singkawang Kalimantan Barat - Riza Linda, Imanuel Tiko Junardi Rafdinal (Universitas Tanjungpura, 2018)
Riparian ecosystem s an area that has ecological potential in supporting river ecosystems. This area is usually overgrown by various types of plants that have adapted to live in a place that is often inundated by river water, especially when it rains. Research on the composition and structure of riparian vegetation in Mount Poteng area was carried out in April - June 2017. The method used in this study was a line method with a combination of paths carried out in 4 locations. The width of each lane is 20 meters and the length is ± 100 meters. Results of the sample plot of 0.03 ha in riparian forest around the Poteng mountain area found a composition of riparian vegetation consisting of 23 species, 21 genera and 19 families. Araceae family is the family that dominates the Mount Poteng riparian area. Tree stand density ranges from 5-60 individuals / ha with diversity index ranging from 0.6 to 1.5.